1991
DOI: 10.1037/0033-295x.98.4.506
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic mental models: A Brunswikian theory of confidence.

Abstract: Research on people's confidence in their general knowledge has to date produced two fairly stable effects, many inconsistent results, and no comprehensive theory. We propose such a comprehensive framework, the theory of probabilistic mental models (PMM theory). The theory (a) explains both the overconfidence effect (mean confidence is higher than percentage of answers correct) and the hard-easy effect (overconfidence increases with item difficulty) reported in the literature and (b) predicts conditions under w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

55
1,084
6
21

Year Published

1992
1992
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,338 publications
(1,186 citation statements)
references
References 76 publications
(120 reference statements)
55
1,084
6
21
Order By: Relevance
“…Gigerenzer et al (1991) asked a similar question following a series of binary choice questions. They found that the average retrospective estimate of the number of correct answers was close to the actual average number correct for a representative sample of questions from the domain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gigerenzer et al (1991) asked a similar question following a series of binary choice questions. They found that the average retrospective estimate of the number of correct answers was close to the actual average number correct for a representative sample of questions from the domain.…”
Section: Resultsmentioning
confidence: 99%
“…Overconfidence may have been the predominant finding in earlier studies because of a tendency for experimenters to construct tests that favored the harder questions in any given domain. The hardest questions in a domain are naturally the most likely to be harder than a reasonable person would expect given his or her knowledge (Gigerenzer et al, 1991;Juslin, 1993;May, 1986).…”
Section: Overconfidence In Interval Estimatesmentioning
confidence: 99%
“…Prior research has found more overconfidence on probabilistic than frequentistic estimations of performance (Gigerenzer et al, 1991).…”
Section: Controllabilitymentioning
confidence: 96%
“…Brunswikian explanations for Trouble with Overconfidence 18 overconfidence hold that overestimation of task performance is an artifact of the way items were selected. The solution to such selection is to establish a reference class with which people are likely to be familiar, and randomly select judgments from that set (Gigerenzer, Hoffrage, & Kleinbölting, 1991). Our theory would offer two explanations for the tendency for overconfidence to go down when problems are randomly drawn from a familiar reference class.…”
Section: Brunswikian Theories Of Overconfidence Ecological Validitymentioning
confidence: 99%
“…Consequently, researchers have tended to ignore that distinction in probability revision tasks. In contrast, for the frequentist interpretation of probability, this distinction is fundamental; and so it seems to be for understanding intuitive reasoning as well (Gigerenzer, 1991b;Gigerenzer, Hoffrage & Kleinbolting, 1991).…”
Section: Research On Deductive and Probabilistic Reasoning: Some Commmentioning
confidence: 99%